Comparison between Dichoptic training and Patching therapy in Amblyopia treatment / Nierbaiza Shuhada Ibrahim - Ibrahim, Nierbaiza Shuhada (2016)
The current approach to the treatment of amblyopia was problematic for a number of reasons. First, there was some issues of compliance to the conventional treatment of amblyopia in which the patching therapy. Current studies had introduced dichoptic training which was a binocular approach that was showing promise in initial clinical studies. However, the effectiveness of the dichoptic training was still being questioned. Thus, the purpose of this study was to identify the comparison between dichoptic training and patching therapy in amblyopia treatment finally to propose a more effective treatment in treating amblyopia patient. This study was done by using the systematic review methods in which the comparison of duration of intervention, technique, training regimen, compliance to treatment, prognosis beyond critical period and improvement in visual functions between the dichoptic training and patching therapy were reviewed from the selected journals and then were tabulated. The results proposed that dichoptic training was a better treatment for amblyopia than patching therapy either in children or adult amblyopia. Although advancements have been made, further research was still required to help those treating amblyopia particularly in regards to improvement and maintaining compliance to treatment, binocular treatment and prognosis of patching therapy beyond the critical period.